Three flames : a novel - Lightman, Alan P., 1948- (Counterpoint, 2019)
"Portrays the struggles of a Cambodian farming family against the extreme patriarchal attitudes of their society and the cruel and dictatorial family father, set against a rural community that is slowly being exposed to the modern world and its values. The book spans the period from 1973, just before the Khmer Rouge genocide, to 2015"--